Control of Papaya Mealybug in Cassava at Namakkal District, Tamil Nadu: A Successful Model of Research- Extension- Farmers Linkage - Sharmila Bharathi, C; B, Mohan; S, Alagudurai; C, Sangeetha; G, Gohila (JOURNAL OF ROOT CROPS, 2015)
Ninety five per cent of the area under cassava in Namakkal district, Tamil Nadu, was severely affected by the papaya mealybug (Paracoccus marginatus) during 2010-2012. The Krishi Vigyan Kendra (KVK), Namakkal of the Tamil Nadu Veterinary and Animal Science University (TANUVAS) established a laboratory for the mass multiplication of the parasitoid (Acerophagus papayae) for the control of papaya mealybug during January 2011 under the scheme sponsored by Agricultural Technology and Management Agency (ATMA), Namakkal. The parasitoid was successfully mass multiplied in the laboratory of the KVK on Paracoccus marginatus colonies by three methods (i) on sprouted potato tubers (ii) on cassava leaves and (iii) on papaya leaves and fruits. Of the three methods, the second instar papaya mealybug infested cassava leaves were found to be very suitable for intensive production of parasitoid in a short period of time. The parasitoids were inoculated on mealy bug infested (second instar larvae) cassava leaves brought by farmers of Namakkal in white plastic boxes and incubated for 15.20 days. The hatched parasitoids were distributed to the farmers with the help of officials from the Department of Horticulture, Namakkal. A total number of 4,44,560 parasitoids were supplied to 2437 farmers covering 3743.2 ha of cassava field. Control of mealybug infestation was noticed from 45 days after the release of parasitoid and complete eradication of the pest could be achieved by the end of six months. There was no mealybug incidence by 2014. Nearly 10 . 15% of parasitoids were found in non host plants.